Optimalisasi Kombinasi Myofascial Release Dengan Oil Ginger Officinale Therapy Terhadap Penurunan Low Back Pain Ibu Hamil Trimester III - Wiwit Desi Intarti; Puri Kresna Wati; Renince Siregar; Rafidah Rahmah; Yuri Zuliani; Evi Oktaviani (Jurnal Ners, 2026)
Low back pain often occurs in pregnant women in their third trimester. This pain can interfere with quality of life. Safe and effective treatment is needed for this problem. This study aims to test the effectiveness of Myofascial Release (MFR) therapy combined with Oil Ginger Officinale Therapy in reducing low back pain in pregnant women in the third trimester. The study used a quasi-experimental design with a pre-test and post-test control group. The sample included 100 pregnant women in Bekasi City who experienced low back pain and met the criteria. The intervention group received both MFR and Oil Ginger Officinale therapy. The control group received only MFR therapy. The intervention was conducted three times a week for one month. Results showed an average pain score of 7.70 in both groups before intervention. After intervention, the pain score fell to 1.26 in the control group and 0.68 in the intervention group. The Independent T-test showed a significant difference between groups (p = 0.0002). In conclusion, the combination of MFR with Oil Ginger Officinale is more effective in reducing low back pain in third trimester pregnant women without side effects. This combination can be recommended as an alternative therapy.